2014
DOI: 10.1177/1357633x14562734
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of telehealth tools and interventions to support family caregivers

Abstract: Summary We conducted a systematic review of studies employing telehealth interventions which focused on family caregivers’ outcomes. The Embase, CINHAL, Cochrane and PubMed databases were searched using combinations of keywords including “telehealth,” “telemedicine,” “telecare,” “telemonitoring,” “caregiver” and “family.” The initial search produced 4205 articles, of which 65 articles met the inclusion criteria. The articles included 52 experimental studies, 11 evaluation studies, one case study and one second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
315
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(331 citation statements)
references
References 70 publications
10
315
1
5
Order By: Relevance
“…The review also found that telehealth implementations made important contributions to the care of patients with chronic diseases, home care, and hospice care [13]. A systematic review about the effectiveness of tele-monitoring in individuals with heart disease evaluated 18 studies and determined that this implementation produced positive results.…”
Section: Evidence-based Practice Implicationsmentioning
confidence: 99%
“…The review also found that telehealth implementations made important contributions to the care of patients with chronic diseases, home care, and hospice care [13]. A systematic review about the effectiveness of tele-monitoring in individuals with heart disease evaluated 18 studies and determined that this implementation produced positive results.…”
Section: Evidence-based Practice Implicationsmentioning
confidence: 99%
“…Many Internet-based materials and opportunities to learn exist for caregivers of patients, for those with MH (dementia, schizophrenia, anorexia) and medical disorders [12]. Services included webcasts, discussion boards, online classes, learning modules, and chat rooms; the best outcomes were best for satisfaction and comfort with services via cell phones [61]. Continuing medical education resources [62] are increasingly available.…”
Section: Methodsmentioning
confidence: 99%
“…However, when it comes to telehealth interventions aimed at family members of adult cancer patients, the picture is less definite. Scoping reviews have been conducted only on web-based interventions or on the effects of eHealth tools for patients and informal caregivers confronted with the problem of cancer [41,45,46], while others have a broader focus on all implemented telehealth tools for family caregivers, but not specifically adopted in cancer care [39]. Therefore, there is still an emerging need of a more complete framework regarding implemented carers' telemedicine tools in all phases of cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…Even though much has been done concerning patient empowerment, more attention is needed on the effects and support of telemedicine on family caregivers and on how promising e-health programmes are in responding to their needs [39,40]. Despite caregivers' requests for provision of support and information competence, a recent meta-review on the effects of eHealth for patients and informal caregivers confronted with cancer concludes that there is a paucity of systematic reviews on this topic and that web-based interventions focused on family members are still an unexplored area [41].…”
Section: Introductionmentioning
confidence: 99%